PLYOMETRICS AND THE EFFECT ON FOUR TYPICAL VERTICAL HEIGHT - Mateescu, Adriana (Arena-Journal of Physical Activities, 2013)
Abstract The aim of this study-case was to determine the effects of plyometric training on height of rise, the (maximal) explosive force of legs, the power of the inferior train. The controlled trial that evaluated the effect of plyometric training on four typical vertical height, test were carried out: Counter Movement Jump - CMJ, Continuous Jump with Bent Legs Reference – CJbref, Continuous Jump with Straight Legs - hCJs, Continuous Jump with Bent Legs - CJb30 sec. Study-case was identified by computerised used Bosco Protocol applied Kistler force platform measurement 9290AD Quattro Jump. The four tests that were performed using Kistler force platform to measure Quatro Jump Bosco Protocol Version 1.0.9.2, gave us the data about the height and jump power and capacity data on neuro-motor recruitment (fast fibers), voluntary effort, fatigue, muscle elasticity effect or stretching. The pooled estimate of the effect of plyometric training o jump height was plyometric training provides a statistically significant and practically relevant improvement in jump height with the mean effect ranging from 3.8 (CJs) to 7.2 (CJb30s).